The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/en14185792
|View full text |Cite
|
Sign up to set email alerts
|

“Where Have I Heard It?” Assessing the Recall of Traffic Safety Campaigns in the Dominican Republic

Abstract: Although traffic crashes are the eighth leading cause of death in the world, and are linked to vehicle and infrastructure-related factors, crash-related fatality rates are much higher in low-income countries. Particularly, the Dominican Republic is the country with the highest accident rate in the whole American continent. Therefore, in the past few years, public agencies have been developing different measures aimed at reducing traffic fatalities, including road safety campaigns. The aim of the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…In the Dominican Republic, they are a tremendously reduced road group. In fact, the latest data indicate that only 1% use bicycles on a daily basis [25]. In countries such as Denmark, the United Kingdom, or Australia, infrastructure improvement for cyclists led to a substantial increase in this type of user [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Dominican Republic, they are a tremendously reduced road group. In fact, the latest data indicate that only 1% use bicycles on a daily basis [25]. In countries such as Denmark, the United Kingdom, or Australia, infrastructure improvement for cyclists led to a substantial increase in this type of user [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should be noted that these types of actions are the ones in which the most significant differences are found according to gender, with females being the ones who prioritize them the most. This is logical given the dynamics of displacement in the country, where there are practically no women drivers [25]. Therefore, they especially demand conditions that are more appropriate to the characteristics of their trips [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of such tools in research can be found in [21,27]. The study [17] was slightly different, as the authors analyzed the state of road traffic safety in a specific country and the impact of non-technical methods on shaping this state.…”
Section: A Brief Overview Of the Content Of This Special Issuementioning
confidence: 99%